Characterization of a Divergent vanD-Type Resistance Element from the First Glycopeptide-Resistant Strain of Enterococcus faecium Isolated in Brazil - Dalla Costa, Libera M. (American Society for Microbiology, 2000)
Enterococcus faecium 10/96A from Brazil was resistant to vancomycin (MIC, 256 μg/ml) but gave no amplification products with primers specific for known van genotypes. A 2,368-bp fragment of a van cluster contained one open reading frame encoding a peptide with 83% amino acid identity to VanH(D), and a second encoding a d-alanine-d-lactate ligase with 83 to 85% identity to VanD. The divergent glycopeptide resistance phenotype was designated VanD4.